Life Histories Center Performance as Response to Text (LEARNing Landscapes, 2020)
Based in anthropology (Cole & Knowles, 2001), life history inquiry into literature emphasizes deep understandings of literary characters that are expressed through dramatic performance. For teachers or teacher-educators, life histories offer a powerful teaching strategy. Life histories support locating readers in a particular pattern or “grammar” of events, situations, and goals while also revealing the subjective worlds of characters who are involved in such events. In an undergraduate Honors Literacies course, life histories performances in response to the young adult novel, The Skin I’m In(Flake, 1998), enabled examinations of the complex interaction of characters, their lives, and particular contexts.
Keywords: reader response; critical texts; character analysis; authentic writing; dramatic performance